Sea sand UHPC and preparation process thereof
Through high-temperature treatment and multi-process modification, high-strength and corrosion-resistant sea sand UHPC were prepared, which solved the durability and quality problems of traditional sea sand UHPC in the case of insufficient or untreated treatment process, and achieved efficient utilization of sea sand resources and environmental protection effects.
Patent Information
- Application Number
- CN202411883859.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-22
AI Technical Summary
In the case of insufficient or untreated treatment process in traditional sea sand UHPC, there are problems such as steel bar corrosion, accelerated carbonization of concrete, shell affecting performance and sulfate reaction, resulting in reduced durability and quality problems.
UHPC is prepared by sea sand, and organic matter and volatile substances are removed through high-temperature treatment. Multiple types of curing modifiers and multiple process modifications are used to prepare high-strength and high corrosion resistance sand, and UHPC with excellent performance is prepared by adjusting the proportion of various types of sand.
It has achieved high strength, high toughness and high durability of sea sand UHPC, solved the problem of scarcity of river sand resources, saved resources and energy, protected the environment, expanded the application areas of sea sand, and enhanced its production value.
Smart Images

Figure CN119859043A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and more specifically, to a sea sand UHPC and a preparation process thereof. Background Art
[0002] At present, the annual amount of sand used in the construction industry is extremely high. Among them, river sand is the main source of natural sand for construction, but the supply of river sand is limited by resources and environmental conditions and is far from meeting the demand. Sea sand has become an important component of construction sand. Sea sand is mainly particles formed by stones in the sea under the impact of waves. This offshore sand resource is widely distributed in my country and has huge reserves. It is the second largest marine mineral resource after shelf oil and natural gas resources. In particular, the construction sand resources widely distributed in the shelf area have great potential and have the realistic possibility of resource utilization. China's sea sand resources can be roughly divided into two categories, one is coastal sea sand distributed on the coast and nearshore waters, and the other is shallow sea sand distributed in the shallow sea of the shelf. Coastal sea sand is mainly distributed in Shandong, Liaoning, Fujian, Guangdong, Guangxi, Hainan and other provinces and regions, and shallow sea sand is mainly distributed in Taiwan Shoal, the eastern mouth of the Qiongzhou Strait, and outside the Pearl River Estuary.
[0003] Since seawater contains sodium salts, magnesium salts, and cadmium salts, sea sand also contains these corrosive salts. Untreated sea sand cannot be used in most buildings. Sea sand contains a high content of chloride salts, which can cause corrosion of steel bars in concrete, thereby reducing the durability of concrete structures. The presence of chloride salts will accelerate the corrosion process of steel bars. When the corrosion rate reaches a certain level, it will cause cracking, peeling, and flaking of the protective layer along the bars, thereby greatly reducing the seismic performance of the steel bars. The crystallization and expansion of chloride salts will accelerate the carbonization process of concrete, which will affect the stability and durability of concrete. Carbonated concrete is more susceptible to erosion by the external environment, leading to structural damage. The sulfates contained in sea sand (mainly Na2SO4) react with Ca(OH)2 in cement to form CaSO4·2H2O hydrate, which then reacts chemically with other components in cement to produce high calcium sulfate aluminate (calcium vanadate), which causes volume expansion and cracking of concrete, greatly affecting the durability of concrete. In addition, sea sand may contain a certain amount of shells, the main component of which is CaCO3. Although they themselves will not react chemically with cement, because the shells are thin flakes, have a smooth surface, and have low compressive strength, they are easy to crack along the joints, resulting in poor adhesion with cement slurry, thus affecting the tensile, compressive, flexural strength, frost resistance, abrasion resistance, and impermeability of the concrete.
[0004] In pursuit of UHPC with excellent performance, traditional sea sand UHPC either requires sand to be cleaned, screened, impurity removed, and re-inspected. The processing technology is not advanced enough, and the processes are time-consuming, resulting in high costs. The multiple processing steps cause large fluctuations in the quality of the processed sand. Or it is directly used in the production of UHPC without any treatment. A large amount of cementitious materials is required to ensure strength and working performance, and high requirements are placed on molding working performance, resulting in difficulty in production control and low production efficiency. Once steel fibers are added, it is easy to clump during mixing, and the concrete has poor workability, making it difficult to construct and easy to rust, which can easily cause quality problems and reduced durability, and increase subsequent maintenance costs.
[0005] Therefore, in view of the above situation, how to utilize sea sand as a resource with higher value has become a research topic for many building materials researchers. Summary of the invention
[0006] The invention discloses a sea sand UHPC, which comprises the following raw materials calculated by weight: 28-49 parts by weight of sulphoaluminate cement, 0.05-0.22 parts by weight of a defoamer, 39-48 parts by weight of mixed sand, 15-40 parts by weight of an admixture, 0.3-0.8 parts by weight of a water reducing agent, and 1-8 parts by weight of fiber.
[0007] Preferably, the mixed sand is prepared by compounding pretreated sea sand, graded quartz sand and graded machine-made sand, and the fineness modulus value of the mixed sand is 2.3 to 2.8;
[0008] The graded quartz sand is composed of quartz sand with a particle size range of 0.1 to 4.75 mm, and the gradation ratio is 2.36 to 4.75 mm: 1.18 to 2.36 mm: 1.18 to 0.1 mm = 1: (2.8 to 3.2): (0.5 to 1);
[0009] The graded machine-made sand is composed of sand with a particle size range of 0.1-4.75 mm, and the grading ratio is 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1).
[0010] Preferably, the silica content of the quartz sand is ≥90%, the mud content is ≤0.5%, the crushing value is ≤10, and the fineness modulus value is 2.3-3.1.
[0011] Preferably, the graded machine-made sand has a crushing value of ≤15, a mud content of ≤0.5%, and a fineness modulus of 2.3 to 3.1.
[0012] Preferably, the sulphoaluminate cement is low-alkalinity L·SAC42.5 sulphoaluminate cement; the admixture is S105 mineral powder, SF90 silica fume or Class I fly ash; and the water reducer is TH-928 polycarboxylate water reducer with a water reduction rate of ≥40%.
[0013] Preferably, the fiber is a steel fiber or a polyvinyl alcohol fiber; the steel fiber has a density of 7.8 g / cm3, a diameter of 0.2-0.3 mm, a major diameter of 50-80, and a tensile strength of >2000 MPa; the density is 1.4 g / cm3, the diameter is 0.05-0.08 mm, the aspect ratio is 50-80, and the tensile strength is >1500 MPa.
[0014] A preparation process of sea sand UHPC includes the following steps:
[0015] Step S1: Select sea sand;
[0016] The grading ratio of sea sand is 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1), and the fineness modulus value is 2.6;
[0017] Step S2: removing impurities;
[0018] Put the sea sand into the calcining furnace, quickly heat it to 900-950℃ and calcine it for 1-2h, then put it into the high-speed mixer and stir it for 30-60min, and then pass it through the cyclone dust collector to eliminate particulate impurities;
[0019] Step S3: heating and pre-activation treatment;
[0020] Put the sea sand treated in the previous step into a heating reactor, and bake it for 1 to 3 hours under the condition of rapidly heating to 500 to 650°C for later use;
[0021] Then, 50% water glass and recovered mud water are uniformly mixed in a ratio of 1:1.5 to obtain a mixed solution;
[0022] Then, the baked sea sand is cooled to 100-150°C and soaked in the mixed solution for 30-60 minutes. The soaked sea sand is taken out and then placed in a drying oven for drying at 105°C.
[0023] Step S4: activation treatment;
[0024] Add the sea sand treated in the previous step into the activation solution and soak for 12 to 24 hours, and filter out the excess liquid from the soaked sea sand;
[0025] Step S5: hot pressing and curing treatment;
[0026] By heating and applying pressure, after the temperature rises to 35°C, kaolin, bentonite and hydrotalcite are added, and after mixing evenly, the temperature continues to rise, and the temperature is controlled between 480 and 760°C, and the pressure is controlled between 10 and 15 MPa;
[0027] Step S6: UHPC molding;
[0028] Pre-dry mix sea sand, mixed sand, sulphoaluminate cement, admixtures and powdered admixtures for 1 to 2 minutes at a speed of 90 to 180 r / min; then add water and other liquid materials for wet mixing, with the wet mixing time being ≥5 minutes, until the mixture approaches the target fluidity; slowly add fiber, and continue stirring after all the fiber has been added, with the stirring time being ≥2 minutes, until the fiber is evenly dispersed in the mixture; the total stirring time is ≤20 minutes.
[0029] Preferably, the sea sand is shallow sea sand in Putian City, Fujian Province.
[0030] Preferably, the activation solution is prepared from KH550 silane coupling agent, methyl diisopropanolamine, sodium thiosulfate, anhydrous alcohol and polymerized polyol.
[0031] Preferably, the powdery admixture contains a silicon-aluminum phase component, and the silicon-aluminum phase component is bentonite or kaolin calcined at 400-800° C., and the mass fraction of Al 2 O 3 is ≥35%.
[0032] The sea sand UHPC of the present invention is prepared from sulphoaluminate cement, defoamer, mixed sand, admixture, water reducing agent and fiber; by using sea sand to make UHPC, and having the performance advantages of high strength, high toughness and high durability, it can not only make full use of sea sand resources, but also solve the problem of scarce river sand resources, which is beneficial to saving resources and energy, and protecting the environment; at the same time, it also broadens the application field of sea sand and improves the production value of sea sand. The sea sand UHPC production process of the present invention is treated at high temperature to remove organic matter and volatile substances, and adopts multiple varieties of curing modifiers and multi-process modification to prepare high-strength and high-corrosion-resistant sand. By adjusting the proportion of various types of sand, various grades of UHPC with excellent performance can be prepared, so as to improve traditional technology and realize efficient utilization of sea sand resources at the same time, and achieve the effect of solving environmental protection problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1The present invention is a schematic diagram of the process of sea sand UHPC and its preparation process. DETAILED DESCRIPTION
[0035] The invention discloses a sea sand UHPC and a preparation process thereof. The UHPC is made of sea sand and has the performance advantages of high strength, high toughness and high durability. It can not only make full use of sea sand resources, but also solve the problem of scarce river sand resources, which is beneficial to saving resources and energy, and protecting the environment; at the same time, it also broadens the application field of sea sand and improves the production value of sea sand.
[0036] The following is a clear and detailed description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The invention discloses a sea sand UHPC, which comprises the following raw materials calculated by weight: 28-49 parts by weight of sulphoaluminate cement, 0.05-0.22 parts by weight of a defoamer, 39-48 parts by weight of mixed sand, 15-40 parts by weight of an admixture, 0.3-0.8 parts by weight of a water reducing agent, and 1-8 parts by weight of fiber.
[0038] UHPC (Ultra-High Performance Concrete) is ultra-high performance concrete. UHPC has extremely high compressive strength, tensile strength and excellent durability, and can maintain stable performance in various extreme environments. High strength: The compressive strength of UHPC can usually reach more than 150MPa, which is much higher than the compressive strength of ordinary concrete. This means that structures built with UHPC can withstand greater pressure and load, greatly improving the safety and stability of the structure. High durability: Due to the dense microstructure of UHPC, its impermeability, freeze-thaw resistance, chemical corrosion resistance and other properties are better than ordinary concrete. This enables UHPC to maintain good performance for a long time in harsh natural environments and extend the service life of the structure. High toughness: By adding steel fibers or synthetic fibers, the tensile strength of UHPC has been significantly improved. This enables UHPC to show better ductility and toughness when subjected to external forces, reducing the risk of structural damage due to brittle fracture. Excellent working performance: UHPC has good fluidity, is easy to cast and form, and has a fast hardening speed, shortening the construction period. At the same time, the self-compacting property of UHPC allows it to achieve a high density without vibration, which improves construction efficiency. UHPC and its components have been vigorously developed in recent years due to their excellent mechanical properties, durability, applicability and economy. It is one of the important fixing materials for construction in high-performance component systems. Making sea sand into UHPC has broad development prospects.
[0039] The sea sand UHPC of the present invention makes its microstructure more compact by precisely controlling the proportion of various raw materials, thereby improving its mechanical properties. In addition, the addition of a water reducer reduces the water-cement ratio and improves the strength and durability of the UHPC. At the same time, the addition of admixtures improves the microstructure of the UHPC and further improves its performance. By introducing fibers, the tensile strength and toughness of the UHPC are improved. These fibers form a stable three-dimensional network structure in the UHPC, effectively preventing the expansion and extension of cracks.
[0040] Preferably, the mixed sand is prepared by compounding pretreated sea sand, graded quartz sand and graded machine-made sand, and the fineness modulus value of the mixed sand is 2.3 to 2.8;
[0041] The graded quartz sand is composed of quartz sand with a particle size range of 0.1 to 4.75 mm, and the gradation ratio is 2.36 to 4.75 mm: 1.18 to 2.36 mm: 1.18 to 0.1 mm = 1: (2.8 to 3.2): (0.5 to 1);
[0042] The graded machine-made sand is composed of sand with a particle size range of 0.1-4.75 mm, and the grading ratio is 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1).
[0043] Preferably, the silica content of the quartz sand is ≥90%, the mud content is ≤0.5%, the crushing value is ≤10, and the fineness modulus value is 2.3-3.1.
[0044] Preferably, the graded machine-made sand has a crushing value of ≤15, a mud content of ≤0.5%, and a fineness modulus of 2.3 to 3.1.
[0045] Preferably, the sulphoaluminate cement is low-alkalinity L·SAC42.5 sulphoaluminate cement; the admixture is S105 mineral powder, SF90 silica fume or Class I fly ash; and the water reducer is TH-928 polycarboxylate water reducer with a water reduction rate of ≥40%.
[0046] Preferably, the fiber is a steel fiber or a polyvinyl alcohol fiber; the steel fiber has a density of 7.8 g / cm3, a diameter of 0.2-0.3 mm, a major diameter of 50-80, and a tensile strength of >2000 MPa; the density is 1.4 g / cm3, the diameter is 0.05-0.08 mm, the aspect ratio is 50-80, and the tensile strength is >1500 MPa. In this embodiment, different fiber materials, such as steel fiber or polyvinyl alcohol fiber, can be selected according to the strength requirements of UHPC.
[0047] Please refer to Figure 1 A preparation process of sea sand UHPC includes the following steps:
[0048] Step S1: Select sea sand;
[0049] The grading ratio of sea sand is 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1), and the fineness modulus value is 2.6;
[0050] Step S2: removing impurities;
[0051] Put the sea sand into the calcining furnace, quickly heat it to 900-950℃ and calcine it for 1-2h, then put it into the high-speed mixer and stir it for 30-60min, and then pass it through the cyclone dust collector to eliminate particulate impurities;
[0052] Step S3: heating and pre-activation treatment;
[0053] Put the sea sand treated in the previous step into a heating reactor, and bake it for 1 to 3 hours under the condition of rapidly heating to 500 to 650°C for later use;
[0054] Then, 50% water glass and recycled mud water are uniformly mixed in a ratio of 1:1.5 to obtain a mixed solution; in this step, the recycled mud water mainly comes from the concrete production and preparation processes such as tanker cleaning, mixing tank cleaning, sand and gravel separation, and site washing. Since these recycled mud waters contain gelling components and admixtures, direct discharge will cause pollution to the environment. In order to further utilize these recycled mud waters, in this step, the recycled mud water and 50% water glass are mixed in proportion. Since the waste water contains a small amount of unhydrated mineral admixtures, hydrated calcium silicate gel, cement and other finer components, this can fill the concrete voids, improve the compactness of the concrete, and thus improve the strength.
[0055] Then, the baked sea sand is cooled to 100-150°C and soaked in the mixed solution for 30-60 minutes. The soaked sea sand is taken out and then placed in a drying oven and dried at 105°C.
[0056] Step S4: activation treatment;
[0057] Add the sea sand treated in the previous step into the activation solution and soak for 12 to 24 hours, and filter out the excess liquid from the soaked sea sand;
[0058] Step S5: hot pressing and curing treatment;
[0059] By heating and applying pressure, after the temperature rises to 35°C, kaolin, bentonite and hydrotalcite are added, and the temperature is continued to rise after being evenly mixed, and the temperature is controlled between 480 and 760°C, and the pressure is controlled between 10 and 15 MPa; kaolin and bentonite are conducive to the solidification of chloride ions, and high temperature and high pressure are conducive to the chemical reaction and physical cross-linking between the activation liquid and the sea sand, thereby improving the surface adhesion and strength of the sea sand. Since this step, the strength, chemical stability, durability and other aspects of the sea sand have been enhanced.
[0060] Step S6: UHPC molding;
[0061] Pre-dry mix sea sand, mixed sand, sulphoaluminate cement, admixtures and powdered admixtures for 1 to 2 minutes at a speed of 90 to 180 r / min; then add water and other liquid materials for wet mixing, with the wet mixing time being ≥5 minutes, until the mixture approaches the target fluidity; slowly add fiber, and continue stirring after all the fiber has been added, with the stirring time being ≥2 minutes, until the fiber is evenly dispersed in the mixture; the total stirring time is ≤20 minutes.
[0062] In the traditional application of sea sand, there are many disadvantages in using sea sand to make concrete, mainly including: chloride ion corrosion of steel bars, accelerated carbonization of concrete, shell content affecting concrete performance and sulfate reaction.
[0063] Chloride ion corrosion of steel bars: Sea sand contains high levels of chloride salts, which can cause corrosion of steel bars in concrete, thereby reducing the durability of concrete structures. The presence of chloride salts will accelerate the corrosion of steel bars. When the corrosion rate reaches a certain level, it will cause cracking along the steel bars, peeling and flaking of the protective layer, thereby greatly reducing the seismic performance of the steel bars.
[0064] Accelerated concrete carbonation: Chloride salt crystal expansion will accelerate the carbonation process of concrete, which will affect the stability and durability of concrete. Carbonated concrete is more susceptible to erosion by the external environment, leading to structural damage.
[0065] The shell content affects the performance of concrete: because the shells are thin flakes, have a smooth surface, and have low compressive strength, they are easy to crack along the joints, resulting in poor adhesion with cement slurry, thus affecting the tensile, compressive, flexural strength of the concrete as well as its frost resistance, abrasion resistance, and impermeability.
[0066] Sulfate reaction: Sulfates contained in sea sand (mainly Na2SO4) react with Ca(OH)2 in cement to form CaSO4·2H2O hydrate, which then reacts chemically with other components in cement to produce high calcium aluminate sulfate (calcium vanadate), causing volume expansion and cracking of concrete, which has a great impact on the durability of concrete.
[0067] It can be seen that the use of sea sand to make concrete will lead to a series of problems such as steel corrosion, accelerated concrete carbonization, performance degradation and reduced durability due to problems such as chlorides and sulfates in it. To this end, the present invention treats sea sand from the following three aspects so that it can be used in the production of UHPC to avoid the above-mentioned problems.
[0068] First, sea sand modification; sea sand is treated at high temperature to remove organic matter and volatile substances, forming stable compounds and reaction products with volcanic ash activity. Some stable compounds adhere to the sand surface and some decomposition products react with the compounds of minerals contained in the sand (forming oxides, nitrates or sulfides on the surface, thereby changing the surface morphology and size and increasing the roughness), thereby increasing the surface roughness of the sand. The increase in the surface roughness of the sand is beneficial to the bonding strength between the sand and the cement stone of UHPC. After treatment in this way, the surface morphology of the sand can be modified, which can well solve the problem of the shell content affecting the performance of concrete.
[0069] Secondly, a variety of curing modifiers and multi-process modification are used to prepare high-strength and high-corrosion-resistant sand. The coupling agent in the modifier has two groups of different properties. Different groups can react with chemical groups on the surfaces of different materials (such as glass, fly ash and other silicon-containing materials) to form strong chemical bonds; even the organophilic groups can react or physically entangle with organic molecules, so that the interface between organic and inorganic materials can be chemically bonded, greatly improving the bonding strength. Other components in the modifier can form secondary reactions with compounds after high temperature to form more stable and stronger compounds attached to the sand surface, thereby further increasing the strength and surface roughness of the sand. The strength of the Yellow River sand soaked in an active agent with silane coupling agent KH-570 as the main component can be increased by 12 to 28 compared with the unsoaked one. After this touch treatment, the modified mineral admixture solidifies the chloride ions and sulfate ions.
[0070] Finally, three types of sand, sea sand, quartz sand and machine-made sand, are combined; various grades of UHPC with excellent performance can be prepared by adjusting the proportions of various types of sand. The traditional mode is to produce different grades of premixes by adjusting the proportions of different admixtures, the proportion of cement dosage and admixtures, the proportion of ultra-fine sand and intermediate sand (such as quartz sand), and the proportion of admixtures and cementitious materials (cement, admixtures). It has the disadvantages of long research and development time, long production and batching time, low quality control and production efficiency, and high cost. The present invention only needs to adjust the proportions of intermediate sand (quartz sand and ordinary machine-made sand) of the same grading and different strengths to produce UHPC of different strength grades.
[0071] After the sea sand is processed through the steps of the present invention, the sea sand can be fully used in the production of UHPC, which expands the application value of the sea sand, has a wide range of production and application fields, and has great advantages in preparing excellent sea sand UHPC. The present invention is further described in detail by examples below:
[0072] Embodiment 1: The grading ratio of sea sand is 2.36mm:1.18mm:1.18mm=1:2.8:0.5, and the fineness modulus value is 2.6; the sea sand is placed in a calcining furnace, and calcined for 1 hour under the condition of rapid heating to 900°C, and then placed in a high-speed mixer for stirring for 30 minutes, and the particulate impurities are eliminated by a cyclone dust collector; the sea sand is placed in a heating reactor, and baked for 1 hour under the condition of rapid heating to 500°C for standby use; then 50% water glass and recycled mud water are uniformly mixed in a ratio of 1:1.5 to obtain a mixed solution; then, the baked sea sand is cooled to 100°C and placed in the mixed solution for soaking for 30 minutes, the soaked sea sand is taken out, and then Put it into a drying box and dry it at 105℃; add the activation liquid to the sea sand and soak it for 12 hours, filter out the excess liquid from the soaked sea sand; heat and apply pressure until the temperature rises to 35℃, then add kaolin, bentonite and hydrotalcite, mix them evenly and continue to heat up, the temperature is controlled at 480℃, and the pressure is controlled at 10MPa; pre-dry mix the sea sand, mixed sand, sulphoaluminate cement, admixtures and powdered admixtures for 1min, and the dry mixing speed is 90r / min; then add water and other liquid materials for wet mixing, the wet mixing time is 5min, until the mixture is close to the target fluidity; slowly add fiber, and continue stirring after all the fiber is added, the stirring time is 2min.
[0073] Example 2: The grading ratio of sea sand is 3.56mm:1.77mm:0.64mm=1:3:0.75, and the fineness modulus value is 2.6; the sea sand is placed in a calcining furnace, and calcined for 1.5 hours under the condition of rapid heating to 925°C, and then placed in a high-speed mixer for stirring for 45 minutes, and the particulate impurities are eliminated by a cyclone dust collector; the sea sand is placed in a heating reactor, and baked for 2 hours under the condition of rapid heating to 575°C for standby use; then 50% water glass and recycled mud water are uniformly mixed in a ratio of 1:1.5 to obtain a mixed solution; then, the baked sea sand is cooled to 125°C and placed in the mixed solution for soaking for 45 minutes, the soaked sea sand is taken out, and then placed in Dry in a drying oven at 105°C; add sea sand to the activation solution and soak for 18 hours, filter out excess liquid from the soaked sea sand; heat and apply pressure until the temperature rises to 35°C, then add kaolin, bentonite and hydrotalcite, mix well and continue to heat up, the temperature is controlled at 620°C, and the pressure is controlled at 12.5MPa; pre-dry mix sea sand, mixed sand, sulphoaluminate cement, admixtures and powdered admixtures for 1.5 minutes at a dry mixing speed of 90r / min; then add water and other liquid materials for wet mixing for 8 minutes until the mixture approaches the target fluidity; slowly add fiber, and continue stirring after all the fiber has been added, and the stirring time is 2 minutes.
[0074] Example 3: The grading ratio of sea sand is 4.75mm:2.36mm:0.1mm=1:3.2:1, and the fineness modulus is 2.6; the sea sand is placed in a calcining furnace, and calcined for 2 hours under the condition of rapid heating to 950°C, and then placed in a high-speed mixer for stirring for 60 minutes, and the particulate impurities are eliminated by a cyclone dust collector; the sea sand is placed in a heating reactor, and baked for 3 hours under the condition of rapid heating to 650°C for standby use; then 50% water glass and recycled mud water are uniformly mixed in a ratio of 1:1.5 to obtain a mixed solution; then, the baked sea sand is cooled to 150°C and placed in the mixed solution for 60 minutes, the soaked sea sand is taken out, and then placed in a drying oven. Dry in a drying oven at 105°C; add sea sand to the activation solution and soak it for 24 hours, filter out excess liquid from the soaked sea sand; heat and apply pressure until the temperature rises to 35°C, then add kaolin, bentonite and hydrotalcite, mix well and continue to heat up, the temperature is controlled at 760°C, and the pressure is controlled at 15MPa; pre-dry mix sea sand, mixed sand, sulphoaluminate cement, admixtures and powdered admixtures for 2 minutes at a dry mixing speed of 180r / min; then add water and other liquid materials for wet mixing for 10 minutes, until the mixture approaches the target fluidity; slowly add fiber, and continue stirring after all the fiber has been added, the stirring time is 4 minutes.
[0075] It should be pointed out that the use of various types of sand to produce and manufacture UHPC has been widely used. However, the use of sea sand as the raw material of UHPC faces many technical challenges. The preparation process provided by the present invention is to improve the inherent defects of sea sand. By using this preparation process, high-quality UHPC can be produced, which greatly alleviates the dilemma of insufficient supply of river sand, improves the utilization rate of sea sand resources, and also protects the ecological environment.
[0076] Preferably, the sea sand is shallow sea sand from Putian City, Fujian Province; depending on the source, the sea sand may contain different amounts of shells, the main component of which is CaCO3. Although they themselves do not react chemically with cement, the shells are flaky, have a smooth surface, and have low compressive strength, so they are easy to break along joints, resulting in poor adhesion with cement slurry, thereby affecting the tensile, compressive, flexural strength, frost resistance, abrasion resistance, and impermeability of concrete. For this reason, the present invention preferably uses shallow sea sand from Putian City, Fujian Province to achieve better compressive strength.
[0077] Preferably, the activation solution is prepared from KH550 silane coupling agent, methyl diisopropanolamine, sodium thiosulfate, anhydrous alcohol and polymerized polyol.
[0078] Preferably, the powdered admixture contains a silicon-aluminum phase component, which is bentonite or kaolin calcined at 400-800°C, and the mass fraction of Al2O3 is ≥35%. The admixture for curing chloride ions mainly adds a silicon-aluminum phase component, which can effectively improve the ability of concrete to cure chloride ions. The component is bentonite and / or kaolin calcined at 400-800°C, and the mass fraction of Al2O3 is ≥35%. The mechanism of action of this component is that the silicon-aluminum phase component can generate Friedel salt (hydrated calcium chloroaluminate) with a purity of more than 90% in an alkaline environment of concrete, realize efficient curing and long-term stability of chloride ions, can significantly reduce the transmission rate of chloride ions inside concrete, and improve the durability and safety of concrete. The use of this component has the following technical advantages: low dosage (15% replacement of cementitious material mass), high chloride ion curing efficiency and long-term stable curing effect.
[0079] Calcined hydrotalcites (LDOs): Studies have shown that calcined hydrotalcites can adsorb a large amount of sulfate ions in the solution and significantly inhibit the formation of calcium sulfoxide and gypsum in the cement hydration environment, effectively delaying the penetration of sulfate ions into the concrete3.
[0080] Sulphoaluminate cement: Sulphoaluminate cement and its composite cement with slag show good overall sulfate resistance.
[0081] The sea sand UHPC of the present invention is prepared from sulphoaluminate cement, defoamer, mixed sand, admixture, water reducing agent and fiber; by using sea sand to make UHPC, and having the performance advantages of high strength, high toughness and high durability, it can not only make full use of sea sand resources, but also solve the problem of scarce river sand resources, which is beneficial to saving resources and energy, and protecting the environment; at the same time, it also broadens the application field of sea sand and improves the production value of sea sand. The sea sand UHPC production process of the present invention is treated at high temperature to remove organic matter and volatile substances, and adopts multiple varieties of curing modifiers and multi-process modification to prepare high-strength and high-corrosion-resistant sand. By adjusting the proportion of various types of sand, various grades of UHPC with excellent performance can be prepared, so as to improve traditional technology and realize efficient utilization of sea sand resources at the same time, and achieve the effect of solving environmental protection problems.
[0082] The above is a detailed introduction to the sea sand UHPC and its preparation process provided by the present invention. For those skilled in the art, according to the ideas of the embodiments of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A sea sand UHPC, characterized in that: The invention comprises the following raw materials calculated by weight: 28 to 49 parts by weight of sulphoaluminate cement, 0.05 to 0.22 parts by weight of a defoamer, 39 to 48 parts by weight of mixed sand, 15 to 40 parts by weight of an admixture, 0.3 to 0.8 parts by weight of a water reducing agent and 1 to 8 parts by weight of fiber.
2. The sea sand UHPC according to claim 1, characterized in that: The mixed sand is prepared by compounding pretreated sea sand, graded quartz sand and graded machine-made sand, and the fineness modulus value of the mixed sand is 2.3 to 2.8; The graded quartz sand is composed of quartz sand with a particle size range of 0.1 to 4.75 mm, and the gradation ratio is 2.36 to 4.75 mm: 1.18 to 2.36 mm: 1.18 to 0.1 mm = 1: (2.8 to 3.2): (0.5 to 1); The graded machine-made sand is composed of sand with a particle size range of 0.1-4.75 mm, and the grading ratio is 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1).
3. The sea sand UHPC according to claim 2, characterized in that: The silica content of the quartz sand is ≥90%, the mud content is ≤0.5%, the crushing value is ≤10, and the fineness modulus value is 2.3-3.
1.
4. The sea sand UHPC according to claim 2, characterized in that: The crushing value of the graded machine-made sand is ≤15, the mud content is ≤0.5%, and the fineness modulus is 2.3-3.
1.
5. The sea sand UHPC according to claim 1, characterized in that: The sulphoaluminate cement is L·SAC42.5 sulphoaluminate cement with low alkalinity; the admixture is S105 mineral powder, SF90 silica fume or Class I fly ash; and the water reducer is TH-928 polycarboxylate water reducer with a water reduction rate of ≥40%.
6. The sea sand UHPC according to claim 1, characterized in that: The fiber is a steel fiber or a polyvinyl alcohol fiber; the steel fiber has a density of 7.8 g / cm3, a diameter of 0.2 to 0.3 mm, a major diameter of 50 to 80, and a tensile strength of >2000 MPa; the density is 1.4 g / cm3, the diameter is 0.05 to 0.08 mm, the aspect ratio is 50 to 80, and the tensile strength is >1500 MPa.
7. The process for preparing sea sand UHPC according to any one of claims 1 to 6, characterized in that: The following steps are included: Step S1: Select sea sand; The grading ratio of sea sand is 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1), and the fineness modulus value is 2.6; Step S2: removing impurities; Put the sea sand into the calcining furnace, quickly heat it to 900-950℃ and calcine it for 1-2h, then put it into the high-speed mixer and stir it for 30-60min, and then pass it through the cyclone dust collector to eliminate particulate impurities; Step S3: heating and pre-activation treatment; Put the sea sand treated in the previous step into a heating reactor, and bake it for 1 to 3 hours under the condition of rapidly heating to 500 to 650°C for later use; Then, 50% water glass and recovered mud water are uniformly mixed in a ratio of 1:1.5 to obtain a mixed solution; Then, the baked sea sand is cooled to 100-150°C and soaked in the mixed solution for 30-60 minutes. The soaked sea sand is taken out and then placed in a drying oven and dried at 105°C. Step S4: activation treatment; Add the sea sand treated in the previous step into the activation solution and soak for 12 to 24 hours, and filter out the excess liquid from the soaked sea sand; Step S5: hot pressing and curing treatment; By heating and applying pressure, after the temperature rises to 35°C, kaolin, bentonite and hydrotalcite are added, and after mixing evenly, the temperature continues to rise, and the temperature is controlled between 480 and 760°C, and the pressure is controlled between 10 and 15 MPa; Step S6: UHPC molding; Pre-dry mix sea sand, mixed sand, sulphoaluminate cement, admixtures and powdered admixtures for 1 to 2 minutes at a speed of 90 to 180 r / min; then add water and other liquid materials for wet mixing for ≥5 minutes until the mixture approaches the target fluidity; slowly add fiber, and continue stirring after all the fiber has been added for ≥2 minutes until the fiber is evenly dispersed in the mixture; Total stirring time ≤20min.
8. The process for preparing sea sand UHPC according to claim 7, characterized in that: The sea sand is shallow sea sand from Putian City, Fujian Province.
9. The process for preparing sea sand UHPC according to claim 7, characterized in that: The activation solution is prepared from KH550 silane coupling agent, methyl diisopropanolamine, sodium thiosulfate, anhydrous alcohol and polymerized polyol.
10. The process for preparing sea sand UHPC according to claim 7, characterized in that: The powdery additive contains a silicon-aluminum phase component, which is bentonite or kaolin calcined at 400-800° C., and the mass fraction of Al2O3 is ≥35%.